The safety and efficacy of the trans-umbilical approach for pyloroplasty in the management of post-acid corrosive gastric outlet obstruction in children - Essam A. Elhalaby; Nezar Abd Erouf Abo Halawa; Ismael E. Elhalaby; Dina Shawky; Hussam Hassan; Hisham A. Almetaher (SpringerOpen, 2021)
Abstract Background Gastric outlet obstruction (GOO) may follow acid corrosive ingestion. Several surgical techniques have been reported after the failure of endoscopic dilatation. The aim of this study was to evaluate the feasibility and safety of Heinecke-Mikulicz pyloroplasty (HMP) through a circum-umbilical skin incision in children with pyloric stricture after accidental acid corrosive ingestion. Results Seven patients were males and 4 were females, their ages ranged from 17 months to 6 years at the time of definitive treatment. The surgery was completed successfully in all patients through the circum-umbilical incision. Vertical extension of skin incision was needed in one patient. The pylorus was grossly affected in 9 patients. Both pylorus and gastric antrum were involved in 2 patients. Nine patients had an excellent postoperative course with the cessation of vomiting and progressive weight gain. One patient developed postoperative recurrent stricture treated by gastrojejunostomy. Another patient with associated esophageal stricture responded to repeated endoscopic dilatation for the esophageal stricture and pyloroplasty for the pyloric stricture. No surgical site infection or wound dehiscence occurred in any patient. Conclusion Heinecke-Mikulicz pyloroplasty through a circum-umbilical approach is both feasible and safe in the majority of children with post-acid corrosive GOO. It is associated with satisfactory wound healing and excellent cosmetic outcome. Different techniques are recommended in cases of severe pyloric stricture associated with significant proximal gastric antral scarring.